SIGNIFIKANSI UU PEMERINTAHAN DAERAH DALAM MENINGKATKAN PARTISIPASI DAN PELAYANAN PUBLIK - Florentinus Sudiran (Pusjar SKPP Lembaga Administrasi Negara, 2006)
The major spirit of the regional autonomy laws of 1999 and 2004 is to empower local potencies. The content and implementation of the laws, however, is perceived to be incompatible to the efforts of promoting people’s engagement in the development processes. The autonomy of arranging household affairs, in fact, goes primarily to and conducted by local authorities. Consequently, the laws have failed to realize the idea of community-centered local government. In the future, therefore, public participation should be reconfirmed not as political opportunity offered by government’s compassion, but as basic service embedded in the government’s functions. Based on theoretical framework, this paper elucidates how could regional autonomy law be an enabling instrument of advancing public participation. Keyword: pemerintahan daerah, partisipasi publik